Application rasch model using R program in analyze the characteristics of chemical items - Untung Desy Purnamasari; Badrun Kartowagiran (Jurnal Inovasi Pendidikan IPA, 2019)
Chemistry is one of the subjects taught in high school. To find out and assess students' understanding regarding chemistry subjects in one semester can be proven by a test. The tests used must have good quality. This study aims to provide information about the characteristics of chemical items test using the Rasch model. Descriptive explorative was used in this study. The subject of the study were tenth grade students in Xaverius Senior High School taken the final semester examination on chemistry subject. The object of this research were  the form of item tests and student answer sheets. Data collection techniques used documentation. Student answer sheets were analyzed using the R program. The results showed that the reliability of the item tests was 0.3 to 0.54 or medium category. Subsequently acquired a good level of difficulty about which amounted to 28 items. In addition, the average student ability is 0.008 with a minimum ability of -2.309 and a maximum of 2.233. ICC and IIC obtained are very accurate in predicting students' abilities. Chemicals items used in the final semester examination  can be used by teachers as a item bank for use in the evaluation of students' abilities. However, there are two items that need to be revised level of difficulty to produce a good question.